Polemik Pengelolaan Tanah dan Kepastian Regulasi di IKN: Sengketa Lahan, Potensi Korupsi, dan Menilik Kembali Investasi - Zaini, Noer Gita Safira; Shalsabilla, Dhillika; Salamah, Ajeng Prameswari; Nisa, Rifa Fadhilahtun (Media Hukum Indonesia (MHI), 2025)
This study focuses on the legal and governance aspects related to land management in the development of the Indonesian Capital City (IKN). This study includes an analysis of nationally applicable regulations, including Law Number 3 of 2022 concerning IKN, Presidential Regulation Number 65 of 2022 concerning Land Acquisition, and other relevant regulations. The type of research used in this study is normative legal research, which focuses the analysis on applicable legal norms by analyzing legal principles, laws and regulations, and court decisions to answer the legal problems studied. This study positions law as an autonomous and structured system of norms, which is not only the basis for regulation but also a means to resolve conflicts in society.